OPTIMASI DISTRIBUSI JARINGAN LISTRIK - Santi Aris Setyaningrum, ; Aditya Prapanca, (Matematika dan Sains, 2009)
The propose of research was to study algorithm simulated annealing applying to re-arrange electrics extension position for the low voltage electrics network distribution with minimization length of cable using Mathlab 7. Data processed were obtained from the PLN electrics distribution data for the regional distribution of Kertajaya Indah Timur Surabaya. The results showed that length of cable needed without simulated annealing was 2300 m, while the length of cable could be decreased till 1600 m by using simulated annealing.